OPTIMALISASI MEDIA PEMBELAJARAN DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM (SKI) DI MI - Zumrotus Sa’diyah; Firda Zakiyatur Rofiah (Jurnal Bahastra, 2020)
The Islamic Cultural History lesson (SKI) is a lesson to discuss past events, so that in the process of teaching and learning activities the teacher uses the storytelling method. Given the character of MI students who are very active, the storytelling method will make students bored, therefore SKI subject teachers are required to be more creative, innovative and progressive in providing learning to students so as to create interesting, fun and impressive learning. One way is to use learning media when teaching, learning media is very helpful for a teacher in conveying the material so that it is easier and more fun for students to understand the lesson. As for the media that can be used in SKI MI learning, there are at least two learning media that can be used, namely visual media which is divided into silent or non-projected visuals and moving or projected visual media. While the use of the second learning media in MI SKI learning is audio-visual media which can be in the form of historical films or documentaries of Islamic Cultural History.